Consumption in Fixed Proportion - Wilson, Edwin B. (Quarterly Journal of Economics, 1945)
Journal Article Consumption in Fixed Proportion Get access Edwin B. Wilson Edwin B. Wilson Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 59, Issue 4, August 1945, Pages 635–639, https://doi.org/10.2307/1883300 Published: 01 August 1945